Challenging and Confronting : The Role of Humanities in Fostering Critical Thinking, Cultural Competency and an Evolution of Worldview in Enabling Education. - Edwards, Lydia; Ritchie, Brendan (Student Success v.13 n.1 p.10-20 https://doi.org/10.5204/ssj.2011, 2022)
Humanities discourse forms part of several Australian academic enabling programs, either embedded within the broader curriculum, or as part of a standalone unit. Within Edith Cowan University's UniPrep course, an introductory Humanities unit is offered to students as one of two electives alongside three other core units. The unit introduces students to key concepts within the Humanities, exploring disciplines such as ethics, philosophy, language, history, religion, politics, law, Indigenous studies and fine arts. In addition to offering students an understanding of these disciplines, studying Humanities within the context of an academic enabling program can provide students with several other benefits. Feedback from students enrolled in the UniPrep Humanities unit indicates that students experience an increased level of cultural competency, an evolution of worldview, and an enhanced level of critical thinking upon completion of the unit. Importantly, these areas align with research conducted into broader academic enabling principles. This article will explore these connections to suggest that the inclusion of Humanities within an academic enabling program can enhance students' preparedness for undergraduate study and life beyond university on several levels. [Author abstract]